Implementation of ICT Management System in Madrasah (Multi-Site Study of State Madrasah Aliyah (MAN) in the District of Central Tapanuli) - Nasution, Putra Mahendra Gunawan; Mesiono, Mesiono; Halimah, Siti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study analyzes the differences and similarities in implementing ICT management systems in MAN Sekabupaten Tapanuli Tengah. This study used qualitative research methods with data collection techniques through observation, interviews, and documentation. The results showed that (1) The difference in planning in MAN 1 is more about problem identification, and MAN 2 is more about achieving goals. In comparison, MAN 3 is more about adjusting the needs of madrasahs, and implementation in MAN 1 prioritizes learning with laptops, projectors, and the internet. At the same time, MAN 2 has not been carried out optimally. At the same time, MAN 3 prioritizes the implementation of learning in mastering office materials, graphic design, and animation, and evaluation in MAN 1 is more about implementing supervision. MAN 2 is more about evaluating results. In comparison, MAN 3 is more about assessment. (2) The planning equation is carried out through teamwork, implementation by utilizing all types of IT based on the madrasah's needs, and evaluation is carried out as material for improvement. This study concludes that there are significant differences and similarities in implementing ICT systems, as assessed by planning, implementation, and evaluation.